2011
DOI: 10.1007/s00064-010-0008-4
|View full text |Cite
|
Sign up to set email alerts
|

Die Versorgung der dorsalen Endphalanxbasisfraktur der Langfinger mittels Hakenplatte

Abstract: From February 2002 to September 2009, 77 mallet fractures type Doyle IVb and IVc were operatively stabilized with a hook plate. In a retrospective study, 59 patients were followed up at a mean interval of 38.3 (3-69) months after the operation. Wound healing problems or inflammation were not observed. Visible disturbances of nail growth were macroscopically seen in 11.9%. Results were very good in 35 patients (59.3%), good in 16 patients (27.1%), sufficient in 5 patients (8.5%), satisfying in 1 patient (1.7%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Unfortunately, the few studies published deal only with a small number of patients, i.e., n = 9 [ 2 ] or n = 13 [ 30 ]. Szalay et al [ 17 ] were the first with a higher number of 59 patients. In their study, nail deformity occurred in 12% using the Stryker hook plate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Unfortunately, the few studies published deal only with a small number of patients, i.e., n = 9 [ 2 ] or n = 13 [ 30 ]. Szalay et al [ 17 ] were the first with a higher number of 59 patients. In their study, nail deformity occurred in 12% using the Stryker hook plate.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the hook plate is a reliable and safe method for treatment of bony avulsion fractures of the distal phalanx as several authors have shown before. Concerning the subjective satisfaction of the patient, the results [ 2 , 17 , 30 ] are good to excellent with only two deficits, which are the cosmetic outcome and the nail deformity. Patients should be informed about this during the informative conversation before giving their informed consent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other disadvantages of open surgery include the skin necrosis caused by skin irritation by the implant, exposing of the implant and nail deformities (1,26). Although this is a common complication in cases with tendinous mallet, there is no sufficient data following soft tissue repair.…”
Section: /mentioning
confidence: 99%